2023
DOI: 10.1371/journal.pone.0293730
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of physicochemical parameters and antibacterial properties of New Caledonian honeys

Marcela Bucekova,
Jana Godocikova,
Romain Gueyte
et al.

Abstract: Honey is an attractive natural product with various health benefits. A few honey-based commercial products have successfully been adopted in clinics to improve wound healing. However, screening of other potential sources of medical-grade honey, in particular, honeys from territories with high floral species diversity and high endemicity, is highly needed. The goal of this study was to characterise the physicochemical and antibacterial properties of New Caledonian honey samples (n = 33) and to elucidate the maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…The MIC and MBC of honey against S. aureus ranged from 5% to 20% (Figure 2), highlighting the sample H4 for its higher antimicrobial activity. These values are in accordance with the results obtained by other authors [23,40,44,45] who found MIC values ranging from 2 to 25%, while other researchers found higher MIC values (between 3 and 50%) [15,39]. Manuka honey assayed by Bucekova [44] showed a 5% MIC value and 10% MBC, similar to MIC for H4 and several MBCs of our honeys.…”
Section: Antimicrobial Activitysupporting
confidence: 93%
See 1 more Smart Citation
“…The MIC and MBC of honey against S. aureus ranged from 5% to 20% (Figure 2), highlighting the sample H4 for its higher antimicrobial activity. These values are in accordance with the results obtained by other authors [23,40,44,45] who found MIC values ranging from 2 to 25%, while other researchers found higher MIC values (between 3 and 50%) [15,39]. Manuka honey assayed by Bucekova [44] showed a 5% MIC value and 10% MBC, similar to MIC for H4 and several MBCs of our honeys.…”
Section: Antimicrobial Activitysupporting
confidence: 93%
“…Other authors found no correlation between antimicrobial activity and H 2 O 2 nor GOx in honeydew honeys, which they related with the presence of catalase, polyphenols, or natural inhibitors of GOx [15,44,46]. Most researchers found correlations between MIC and H 2 O 2 concentrations [13,39,40] and between MIC and GOx activities [45], concluding that the antimicrobial properties of honey depend on the accumulation of H 2 O 2 .…”
Section: Antimicrobial Activitymentioning
confidence: 97%